Ipseidade e alteridade em Sartre - Bet, Luiz André Colonetti (Universidade Federal de São Carlos, 2015)
This work aims, through an analysis of the Sartre’s pre-reflective cogito, verify how is implicit in the structures of the being-for-itself (consciousness) the presence to itself, the presence to the other (otherness) and the presence to the world. For this, will be explored some notions connected directly to the concept of consciousness, such as intentionality, human reality, image, ego, nihilation, being-in-itself, being-for-itself, being-for-other, among others, as well as how these concepts are engendered so arises, within the cogito itself, otherness and the world. In other words, how the circuit of ipseity, to say the very personhood, indicates the presence of the other and the world. For this, we shall discuss certain works of the early period of philosophical publications of Sartre, Situations I (especially the article on Husserl, titled A fundamental idea of phenomenology of Husserl: intentionality), The Transcendence of the Ego, The Imagination, The Imaginary and a few chapters of Being and Nothingness dealing with the issue which this study aims to investigate.
Ipseity and alterity in Sartre
Keywords: Consciência; Ipseidade; Alteridade; Cogito pré-reflexivo; Intersubjetividade; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA